Epidemiologia molecular de Escherichia coli e Klebsiella spp produtoras de beta-lactamase de espectro ampliado - Wollheim, Cláudia (My University, 2014)
The extended-spectrum beta-lactamases (ESBL) represent an important mechanism of resistance to beta-lactam antibiotics. Such enzymes have spread among members of the Enterobacteriaceae family, which are responsible for infections related to health care, particularly nosocomial infections. Objectives: (a) To determine the prevalence of ESBL producing Escherichia coli and Klebsiella spp of hospital and community origin; (b) To verify the origin of the isolates (clinical sample and internment unit); (c) To evaluate the accuracy of the phenotypic tests for ESBL detection; (d) To determine the sensitivity profiles to antimicrobial drugs; (e) To identify the beta-lactamase genes; (f) To evaluate the dissemination way and; (g) To perform experiments of resistance transfer. Materials and Methods: 1,346 isolates were evaluated (1,162 E. coli, 180 K. pneumoniae and 4 K. oxytoca), from inpatient and outpatients, between April 2003 and May 2006, in Caxias do Sul. One isolate/patient was included and the nosocomial infection defined by the CDC (Centers for Diseases Control and Prevention). By means of the disc-diffusion method, according to the CLSI (Clinical and Laboratory Standards Institute), the ESBL producers were identified (screening: aztreonam, cefotaxime, ceftazidime, ceftriaxone, and cefpodoxime and confirmation: cefpodoxime, ceftazidime, cefotaxime, with and without clavulanic acid). Cefepime was included in the tests. The isolates were submitted to sensitivity tests to antimicrobial drugs, using disc-diffusion, defined by CLSI; to PCR for detecting the bla TEM, bla SHV, bla CTX-M genes, and; to PGFE typification. The E. coli a-DH strain was used as the receptor in conjugation experiments and the transconjugants were analyzed with regards to ESBL production and sensitivity profile. Results: The ESBL prevalences at the hospital level were: K. pneumoniae (43.7%) and E. coli (6.7%) and at the community, 2.6% and 0.4%, respectively. The airways (sputum, traqueal aspiration and broncoalveolar lavage), blood, and urine, and the ICUs and surgical units were the clinical samples and the internment units presenting the largest percentages of ESBL producing isolates. Independently of the bacterium, ceftazidime was the substrate which provided the poorest results in the tests. On the other hand, cefpodoxime, cefotaxime, ceftriaxone, and aztreonam showed 100% sensitivity and specificity >94.0% for Klebsiella spp isolates. For E. coli, the best substrate was cefpodoxime (100% sensitivity and 75.0% specificity). Cefepime presented excellent performance. The ESBL producing Klebsiella spp isolates showed higher resistance rates than the ESBL non-producing strain, for several antimicrobial drugs, either beta-lactamic or not. Irrespectively of ESBL production, these isolates showed sensitivity to carbapenems and tigecyiclin. In the E. coli and Klebsiella spp with the ESBL phenotype, the beta-lactamase genes blaTEM (89.0%), blaCTX-M (75.6%) e blaSHV (35.4 %). Were detected. 22 PFGE patterns were identified, 11 with more than one isolate. These clones comprised 50 isolates of ESBL producing K. pneumoniae, with high intra-hospital dissemination among the internment units and for times longer than one year. The transconjugants presented the ESBL phenotype and resistance to aminoglycosides. Conclusions: Our results have shown that ESBL production constitutes an essentially nosocomial problem. We conclude that the addition of cefepime to the ESBL detection tests significantly enhances the accuracy of the test when applied to E. coli. However, the ESBL producing isolates of the genus Klebsiella represent the main problem in the hospital. These isolates presented great genomic variability, indicating strong selective pressure by antimicrobial drugs, but also multiclonal dissemination, which indicates cross-transmission and an endemic situation of these bacteria in the hospital. Finally, our results indicate an easy spreading of multi-resistant plasmids, what can represent an important impact on the therapeutic options for the treatment of ESBL producing bacteria.
As beta-lactamases de espectro ampliado (ESBL) representam um importante mecanismo de resistência aos beta-lactâmicos. Essas enzimas disseminaram-se entre membros da família Enterobacteriaceae que causam infecções relacionadas à assistência à saúde, especialmente as nosocomiais. Objetivos: (a) Determinar a prevalência de Escherichia coli e Klebsiella spp produtores de ESBL de origem hospitalar e comunitária; (b) Verificar a origem dos isolados (amostra clínica e unidade de internação); (c) Avaliar a acurácia dos testes fenotípicos de detecção de ESBL; (d) Determinar os perfis de sensibilidade aos antimicrobianos; (e) Determinar os genes de beta-lactamase; (f) Avaliar o modo de disseminação e; (g) Realizar experimentos de transferência de resistência. Material e métodos: Foram avaliados 1346 isolados (1162 E. coli, 180 K. pneumoniae e 4 K. oxytoca), de pacientes internados e ambulatoriais, entre abril de 2003 a maio de 2006, em Caxias do Sul. Um isolado/paciente foi incluído e a infecção hospitalar definida pelo CDC (Centers for Diseases Control and Prevention). Pelo método disco-difusão, conforme CLSI (Clinical and Laboratory Standards Institute) identificou-se os produtores de ESBL (triagem: aztreonam, cefotaxima, ceftazidima, ceftriaxona e cefpodoxima e confirmatório: cefpodoxima, ceftazidima, cefotaxima, com e sem ác. clavulânico). A cefepima foi incluída nos testes. Os isolados foram submetidos a testes de sensibilidade aos antimicrobianos, por disco-difusão, segundo a CLSI; ao método de PCR para detecção dos genes bla TEM, bla SHV, bla CTX-M e; à tipagem por PGFE. A cepa E. coli αDH, como receptora, foi usada na conjugação e os transconjugantes pesquisados para produção de ESBL e perfil de sensibilidade. Resultados: As prevalências de ESBL em nível hospitalar foram: K. pneumoniae (43,7%) e E. coli (6,7%) e a comunidade, respectivamente, de 2,6% e 0,4%. As vias aéreas (escarro, aspirado traqueal, lavado broncoalveolar) , sangue e urina, e as UTIs e Clínica-Cirúrgicas foram as amostras clínicas e unidades de internação com os maiores percentuais de isolados produtores de ESBL. Independente da bactéria analisada, a ceftazidima foi o substrato com o pior desempenho nos testes. Já a cefpodoxima, a cefotaxima, a ceftriaxona e o aztreonam apresentaram sensibilidade de 100% e especificidade >94,0% para isolados de Klebsiella spp. Para E. coli a cefpodoxima foi o melhor substrato (sensibilidade de 100,0% e especificidade de 75,0%). A cepefima apresentou excelente desempenho. Os isolados de Klebsiella spp produtores de ESBL apresentaram taxas de resistência superiores àqueles apresentados pelos isolados não produtores de ESBL, para vários antimicrobianos beta-lactâmicos e não beta-lactâmicos. Independente da produção de ESBL esses isolados foram sensíveis aos carbapenêmicos e tigeciglina. Foram detectados em E. coli e Klebsiella spp com fenóitpo ESBL os genes de beta-lactamase blaTEM (89,0%), blaCTX-M (75,6%) e blaSHV (35,4%). Foram identificados 22 padrões de PFGE, sendo 11 com mais de um isolado. Esses padrões envolveram 50 isolados de K. pneumoniae produtores de ESBL, com alta disseminação intra-hospitalar entre as unidades de internação do hospital e por período superior a um ano. Os transconjugantes apresentaram fenótipo de ESBL e resistência aos aminoglicosídeos. Conclusões: Nossos resultados mostraram que a produção de ESBL constitui um problema essencialmente nosocomial. Concluímos que a adição da cefepima nos testes de detecção de ESBL leva a um aumento significante na acurácia para E. coli. No entanto, os isolados produtores de ESBL do gênero Klebsiella representam o maior problema no hospital. Esses apresentaram ampla variabilidade genômica, indicando forte pressão seletiva de antimicrobianos, mas também disseminação multiclonal, indicando transmissão cruzada e uma situação de endemia dessas bactérias no hospital. Por fim, nossos resultados indicaram uma fácil disseminação de plasmídeos multirresistentes, o que pode representar um impacto importante nas opções terapêuticas para o tratamento de infecções por bactérias produtoras de ESBL.
Keywords: Epidemiologia; Microbiologia médica; Epidemiologia molecular